Korthalsella japonica (Viscacae): New Record for the Nepal Himalayas - Devkota, Mohan Prasad; Joshi, Giri Prasad (Ecoprint: An International Journal of Ecology, 2009)
Korthalsella japonica (Thunb.) Engler (Viscaceae) mistletoe is reported as a new record for the Nepal Himalayas. Key words: Korthalsella japonica, Viscaceae, mistletoe, Nepal Himalayas. doi: 10.3126/eco.v15i0.1948 ECOPRINT 15: 89-90, 2008